2016
DOI: 10.1038/nature19800
|View full text |Cite
|
Sign up to set email alerts
|

Formation of new chromatin domains determines pathogenicity of genomic duplications

Abstract: Chromosome conformation capture methods have identified subchromosomal structures of higher-order chromatin interactions called topologically associated domains (TADs) that are separated from each other by boundary regions. By subdividing the genome into discrete regulatory units, TADs restrict the contacts that enhancers establish with their target genes. However, the mechanisms that underlie partitioning of the genome into TADs remain poorly understood. Here we show by chromosome conformation capture (captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
561
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(601 citation statements)
references
References 37 publications
21
561
1
1
Order By: Relevance
“…Irrespective of the mechanisms underlying their formation, genetic evidence suggests that TADs contribute to establish correct interaction patterns between enhancers and promoters (Symmons et al 2014;Lupiáñez et al 2015;Franke et al 2016). Consistent with this, transcriptional coregulation of neighboring genes is favored within TADs during differentiation (Nora et al 2012) and upon transcriptional responses to external stimuli (Le Dily et al 2014).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Irrespective of the mechanisms underlying their formation, genetic evidence suggests that TADs contribute to establish correct interaction patterns between enhancers and promoters (Symmons et al 2014;Lupiáñez et al 2015;Franke et al 2016). Consistent with this, transcriptional coregulation of neighboring genes is favored within TADs during differentiation (Nora et al 2012) and upon transcriptional responses to external stimuli (Le Dily et al 2014).…”
mentioning
confidence: 66%
“…Several studies have provided evidence on the fundamental role of compartmentalization into TADs to instruct enhancer-promoter communication (Nora et al 2012;Symmons et al 2014;Lupiáñez et al 2015;Franke et al 2016), but they remain elusive on what makes TADs 'special' compared to other chromosomal folding layers, such as sub-TADs and notably contact domains or meta-TADs. In this study, we present a new domain-calling algorithm that is able to segment Hi-C interaction maps into nested sets of The number of sublevels in a domain correlates with the transcriptional activity within the domain (shown for domains at 65% RI in ESC).…”
Section: Discussionmentioning
confidence: 99%
“…As TADs and CDs likely represent orthogonal measures of the same structural units, we use the term TADs unless specifically referring to published data sets employing the CD approach. Topological constraints imposed by TADs favor looping interactions to cis-regulatory element:gene pairings within the same TAD (Lupianez et al 2015;Franke et al 2016;Hnisz et al 2016). However, a higher level of genome organization also occurs where multiple TADs many megabase pairs distal on one chromosome or on different chromosomes can be adjacent and share a functional state (Lieberman-Aiden et al 2009).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Understanding how enhancers 20 regulate gene expression is therefore essential to understand how organisms develop and function throughout life. In fact, disruption of enhancer function has been shown to lead to abnormal gene expression and thus to diseases [4][5][6][7][8] . In addition, the majority of variants identified in Genome Wide Association Studies (GWAS) are found outside coding sequences 9,10 .…”
mentioning
confidence: 99%